Treating Parry-Romberg Syndrome Using Three-Dimensional Scanning and Printing and the Anterolateral Thigh Dermal Adipofascial Flap. Issue 6 (September 2015) - Chai, Gang; Tan, Andy; Yao, Caroline A.; Magee, William P.; Junjun, Pan; Zhu, Ming; Bogari, Melia; Hsu, Yulung; Xu, Haisong; Zhang, Yan
<x xml:space="preserve">Abstract</x> Background: As three-dimensional technology becomes more ubiquitous, many plastic surgical applications have emerged. The authors investigate a three-dimensional scanning and printing system for facial soft tissue reconstruction in conjunction with an anterolateral thigh dermal adipofascial flap for the treatment of Parry-Romberg syndrome. Methods: Seven patients with facial atrophy of the zygomatic, buccal, and mandibular areas were included. Three-dimensional scanning of each patient's face in conjunction was analyzed with computer-aided design (CAD) to quantify areas of facial asymmetry. Models were then created using three-dimensional printing to map areas of soft tissue deficiency. Free anterolateral thigh (ALT) dermal adipofascial flaps were designed based on the three-dimensional models of soft tissue deficiency. Results: All flaps survived. One case had a postoperative hematoma. Six patients had restored facial symmetry. One patient required fat injections to obtain symmetry. No patients required revision surgery of their healed flaps for contouring. Conclusions: Three-dimensional laser scanning and three-dimensional printing in combination with a free ALT dermal adipofascial flap offer surgeons a precise means to reconstruct facial contour deformities.